Nutrição potássica e cálcica como estratégia mitigadora do estresse salino no cultivo de melões nobres em ambiente protegido - Oliveira, Renata Ramayane Torquato (Universidade Federal Rural do Semi-Árido, 2021)
Fertigation management strategies with the enrichment of certain nutrients, such as potassium and calcium, have been studied to enable the use of saline waters in agriculture. However, these studies are not well understood as to the K:Ca ratios that attenuate the effects of the use of saline water on ‘noble’ melons produced in a protected environment. Therefore, the present study was conducted to evaluate fertigation with different K:Ca ratios as a strategy to mitigate salt stress in ‘noble’ melons in protected cultivation. The experimental design used was in randomized blocks, with treatments arranged in a 3x6 factorial scheme, corresponding to three melon cultivars (Cantaloupe - Bazuca hybrid; Gália - McLaren hybrid; Orange - County hybrid) fertigated with six nutrient solutions [S1 - standard nutrient solution (SNP); S2 - SNP + NaCl (5.0 dS m-1); S3 - S2 enriched with K (50%); S4 - S2 enriched with K (100%); S5 - S2 enriched with Ca (50%); S6 - S2 enriched with Ca (100%)]. Throughout the experiment, plants were evaluated for growth parameters nondestructively (plant height, stem diameter, number of leaves and leaf area) and, at the end of the experiment, destructively (leaf dry mass, stem dry mass, fruit dry mass and total dry mass). After harvest, the fruits were evaluated for production parameters (weight, diameter, internal cavity and pulp thickness) and quality parameters (pulp firmness, soluble solids content, titratable acidity, ratio between soluble solids and titratable acidity and vitamin C). The data were subjected to analysis of variance and analyzed by Tukey test (p ≤ 0.05). According to the results obtained, it was observed that the three cultivars were sensitive to salt stress. However, among the cultivars studied, McLaren was more tolerant for presenting less reduction in the weight of the fruits. It was also observed that the nutrient solutions with potassium and calcium did not mitigate the negative effect of salinity on growth, but fertigation with nutrient solution enriched with potassium at 50% promoted improvements in production and quality parameters, by increasing pulp thickness, soluble solids content and the ratio between soluble solids and titratable acidity, under salinity conditions
Keywords: Cucumis melo L.; Curcubitaceae Estresse salino; Potássio Cálcio; Cucumis melo L.; Cucurbitaceae Salt stress; Potassium Calcium; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO